Brain oscillatory responses in patients with bipolar disorder manic episode before and after valproate treatment - Özerdem, Ayşegül; Güntekin, Bahar; Tunca, Zeliha; BAŞAR, EROL (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2008)
Background: GABA/Glutamatergic dysfunction and neural circuits which regulate cognitive processing are involved in the underlying pathology of bipolar disorder. Event related oscillatory neuroelectrical activity reflects integrative brain functioning, different frequency bands representing different cognitive functions. Methods: Event Related Potentials to visual odd-ball paradigm in ten manic/hypomanic medication free, DSM-IV bipolar patients were measured before and after six weeks of valproate monotherapy in comparison to ten sex and age matched healthy controls. Different frequency band responses were obtained by digital filtration of ERPs. Young mania rating scale (YMRS) was used to assess clinical response. Repeated measures ANOVA, Wilcoxon and Mann Whitney U tests were used for statistical analysis. Results: Patients showed significantly higher baseline occipital beta (1830 Hz) (p: 0.014) response than healthy controls. They were devoid of the occipito-frontal alpha (8-13 Hz) dominance presented by the control group. Occipital beta response reduced significantly (p: 0.009) and became similar to controls after treatment. Post-treatment alpha responses were significantly lower than baseline in anterior temporal (p: 0.038) and occipital (p: 0.027) locations. Healthy controls displayed a significantly increased frontal alpha response at the second assessment but the patients did not. Mean YMRS score reduced significantly compared to baseline at the end of six weeks (P: 0.004). Conclusions: Alpha response is the universal operator in the brain. Increased occipital beta response in mania may be compensatory to the dysfunctional alpha operation. its reduction after valproate may be through modulation of glutamatergic and GABAergic mechanisms and indicate medication's corrective effect on the underlying pathogenesis. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Bipolar Disorder; event related oscillations; alpha oscillations; beta oscillations; neurocognitive functioning; valproate; GABA/glutamate; event-related potentials; mood disorders; schizophrenia-patients; auditory-stimulation; cognitive-processes; neural synchrony; gamma activity; rating-scale; dysfunction; neuroanatomy; bipolar bozukluk; olaya ilişkin salınımlar; olaya ilişkin salınımlar; alfa salınımlar; beta salınımlar; bilişsel işleyişi; GABA / glutamat; olaya ilişkin potansiyeller; duygudurum bozuklukları; Şizofreni hastaları; işitsel-stimülasyon; bilişsel süreçler; nöral senkronizasyonu; gama aktivitesi; değerlendirme ölçeği; fonksiyon bozukluğu; nöroanatomi